Merajut Kohesi Nasional: Etno-Nalisonalisme Dan Otonomi Daerah Dalam Proses Demokratisasi - Purwo Santoso (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Uncritical understanding of the notion of nation-state in Indonesia has led a discredit to ethno-nationalism, which essentially is the primary form of nationalism in favour of the secondary form of nationalism. The former refers to a shared imagination of being a member of ethnic group, and the later refers to a shared feeling of being a citizen of the state. Such a mistreatment of ethno-nationalism in governing the state has troubled the state itself as demand of more local autonomy sprang out. It is through a process of political decentralization that the state attempt to accommodate demand for expressing ethno-nationalism. The difficult process of negotiating transition toward a democratic order in Indonesia is eased by the state's capability to redefine the meaning of nationalism and local autonomy.